2018
DOI: 10.1155/2018/4657420
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of ACO (Asthma-COPD Overlap) in Aboriginal People

Abstract: Background and Objective Aboriginal peoples are at a higher risk of many chronic respiratory diseases compared to the general Canadian population. Patients with asthma-COPD overlap (ACO), a disease newly described in 2015, are associated with frequent exacerbations, rapid decline in lung function, poor quality of life, high mortality, and disproportionate utilization of health-care resources than patients with asthma and COPD alone. The objective was to investigate the prevalence and risk factors of ACO in Abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The study characteristics of the included studies are summarized in Table 2. In total, we included 27 studies published since 2011, except for one study that published in 1996: twelve from Europe [10, 12, 13, 16, 17, 20, 23, 25, 2830, 35], nine from the North America (United States and Canada) [11, 15, 18, 21, 26, 27, 3234], three East Asia (China and Korea) [19, 22, 36], three from the Latin America and 6 low- and middle-income countries and Australia [14, 24, 31]. The majority of the included studies were published after 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics of the included studies are summarized in Table 2. In total, we included 27 studies published since 2011, except for one study that published in 1996: twelve from Europe [10, 12, 13, 16, 17, 20, 23, 25, 2830, 35], nine from the North America (United States and Canada) [11, 15, 18, 21, 26, 27, 3234], three East Asia (China and Korea) [19, 22, 36], three from the Latin America and 6 low- and middle-income countries and Australia [14, 24, 31]. The majority of the included studies were published after 2015.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 A previous self-reported survey among Canadian Indigenous people observed that prevalence of asthma/COPD overlap could be higher among Indigenous people. 48 The findings of our study indicate that among Indigenous Australians, conditions other than asthma or concurrent presence of asthma and COPD, 23,24 or bronchiectasis alongside asthma 25 could explain the apparently high rates of self-reported asthma in previous population surveys.…”
Section: Discussionmentioning
confidence: 61%
“…This retrospective cohort study analyzed the effects of statins, ICS, and OS exposure on patients with ACO. The prevalence of ACO among young adults was found in many studies in the real world (de Marco et al, 2013; de Marco et al, 2015; Ekerljung et al, 2018), especially in the aboriginal population (Koleade et al, 2018). We identified patients aged 20 years and above with ACO and diagnosed with COPD ( ICD-9-CM codes 491, 492, and 496) from January 1, 2000, to December 31, 2010.…”
Section: Methodsmentioning
confidence: 93%